Perbaikan Mutu Bubuk Kakao Melalui Proses Ekstraksi Lemak dan Alkalisasi - Heru Prono Widayat (Jurnal Teknologi dan Industri Pertanian Indonesia, 2013)
“This study aimed to investigate the possibility of reducing the fat content of cacao powder by using organic solvent extraction and to improve the cacao powder quality that meets the quality standard and market requirement. The research was carried out at the University of Syiah Kuala from September 2007 to November 2007. Fermented cacao beans as raw material for the research were collected from farmers in Seureuke, Aceh Utara. Cacao fat was extracted from the powder by pressing them at high pressure. Remaining fat in the powder was further reduced by organic solvent extraction to approximately 4 percent to meet the Indonesian National Standard (SNI). The cacao powder was alkalized with variation treatments of potassium carbonate concentration of 2.0, 2.5 and 3.0 percent and alkalization time of 15, 30 and 45 minutes. The experiment was designed according to randomized factorial design with three replications.Alkalization had affected pH and solubility of cacao powder significantly. pH of the powder increased proportionally as followed the function of y=0.35x + 5.00. The effect of alkalization to the solubility was quadratic with a function of y= -16.34x2 + 76.93x – 60.60. The maximum solubility of 30% was reached at the concentration of potassium carbonate of 2.35%.The alkalization affected the colour hue L* of the cacao powder. Addition of potassium carbonate and time of alkalization had a significant effect but no effect on the interaction. The effect of potassium carbonate and time of alkalization followed the function of y= -4.39x + 42.17 and y= -0.13x + 35.17 respectively. Aroma of alkalized cacao powder was better than commercial products from the market. This had been investigated by panellist consisting of 20 people.